Dermoscope-guided excisional biopsy in a child with CD68+ and S100- juvenile xanthogranuloma - Chuh, A.; Klapper, W.; Zawar, V.; Fölster-Holst, R. (European Journal of Pediatric Dermatology, 2017)
A seven-year-old boy had a cutaneous mass on the anterior aspect of his right thigh, with dermoscopy revealing lobules which might be enlarged dermal papillae. We performed a dermoscope-guided excisional biopsy for high precision, with histopathology and immunohistochemistry revealing a CD68+ and S100- juvenile xanthogranuloma. To our best knowledge, this is the first reported dermoscope-guided surgery on a child.